Investigating The Index and Physical Properties of Soils to Be Used as Subgrade Material (In Case of Gilgel-Beles, Ethiopia) - Tolossa Jote Denbi; Tarekegn Reta Mesfin (Peerian Journals Publishing, 2022)
Investigating the index properties and identifying the characteristic of the soil is very important for construction works as well as for further studies in the future as an input. The properties of the soil such as plasticity limit, liquid limit and plastic index of the soil are basic properties of the soils; which affect the design in highway construction. The objective of this research was to know the index, physical properties of soils and classify the soils on basis of their properties through Gilgel-beles town. To achieve the objective of this study, disturbed and undisturbed samples from different parts of the town were collected. To determine the properties of soil the test was conducted by using ASTM standard test procedure. Based on the laboratory test results the properties of soils of the study area were specific gravities range from 2.6 to 2.72, clay fraction 23-54.6%, silt fraction 14.9-50.5%, sand fraction 20.82-39.1% and gravel fraction 0-1.4%, liquid limit 30 – 52.5%, plastic limit, 24.9 – 40.5% and plastic index 5 – 19.5%. The test results showed that the soil found in the study area from all samples are almost fine grained soil consisting of sand in nature. According to USCS classification system of plasticity chart, most of the soil of the study area falls below A-Line in ML region, and TP-3, TP-5 and TP-7 in MH region, which have high plasticity (LL>50%) and the classification soils found in Gilgel-Beles town were ML, MH and CL. And also, according to AASTHO soil classification, the study area soils were dominantly categorized in A-7-5 and A7-6 which is poor for sub-grade materials. Based on the compaction test, maximum dry density (MDD) ranges from1.57 to 1.81 g/cm3 with optimum moisture content from 17 to 35.38 %. which is poor for sub-grade materials
Keywords: Investigating; index; physical; Gilgel-Beles